Heat transfer enhancement of a double pipe heat exchanger by Co-Twisting oval pipes with unequal twist pitches. (December 2021) - Luo, Chao; Song, KeWei; Tagawa, Toshio
Abstract: A double pipe heat exchanger composed of two co-twisting oval pipes with unequal twist pitches is proposed in this paper. The fluid flow and heat transfer characteristics are numerically studied for the twist pitch ratio of the outer to inner pipes ranging from 1.0 to 2.0 in the laminar regime. The results show that the heat transfer first increases and then decreases with the increase of twist pitch ratio. The corresponding increase in flow resistance is relatively less than the increase in heat transfer. The largest differences in Nusselt number and friction factor between different twist pitch ratios are 71.4% and 19.0%, respectively. The heat transfer enhancement is the largest when the twist pitch ratio is 1.5. The Nusselt number is enhanced by 97.0% with friction factor only increasing by 43.7% compared with the simple straight annular pipe. For the optimal twist pitch ratio 1.5 in terms of the best thermal performance, the highest thermal performance factor is 1.75 times as large as the simple straight annular pipe. Fitted correlations are also proposed with the deviations within ±12% for Nusselt number, ±6% for friction factor, and ±8% for thermal performance factor.